Perspective—Electrochemical Stability of Water-in-Salt Electrolytes. Issue 7 (23rd March 2020) - Kühnel, Ruben-Simon; Reber, David; Battaglia, Corsin
Abstract : The water-in-salt approach has expanded the electrochemical stability window of aqueous electrolytes, enabling novel aqueous batteries with relatively high cell voltages and energy densities. However, the stability of these electrolytes tends to be overestimated. The instability of the electrolyte is typically masked by high rates and a large excess amount of electrolyte present in lab cells. Based on a discussion of practical cells, we revisit voltammetry data and offer guidelines for a more stringent evaluation of electrochemical stability window data.